2013
DOI: 10.1111/ijfs.12205
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of lipid and protein oxidation, total iron content and fatty acid profile of conventional and organic pork

Abstract: Summary The aim of the research was to compare differences in lipid and protein oxidation, total iron content and fatty acid profile in pork loin obtained from organic and conventionally reared pigs. The samples of organic meat were taken from breeding certified by the polish certifying body according to the Council Regulation (EC) no 834/2007 on organic production and labelling of organic products. The meat samples were examined at the following times post‐mortem: 2, 4, 7 days. Measurements of lipid oxidation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…The heme iron content was determined after extraction with acidified acetone solution following the analytical conditions described by Karwowska and Dolatowski [18]. The absorbance of extract was measured at 640 nm in a UV-VIS spectrophotometer (Nicolet Evolution 300, Thermo Electron Corporation, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The heme iron content was determined after extraction with acidified acetone solution following the analytical conditions described by Karwowska and Dolatowski [18]. The absorbance of extract was measured at 640 nm in a UV-VIS spectrophotometer (Nicolet Evolution 300, Thermo Electron Corporation, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The total pigments, heme iron and nitrosylmyoglobin content were determined according to the procedure proposed by Hornsey [16] with a slight modification according to Karwowska and Dolatowski [17]. The amount of total pigments and heme iron content were calculated according to Lee et al [18] and expressed in ppm.…”
Section: Total Pigments Heme Iron and Nitrosylmyoglobin Contentmentioning
confidence: 99%
“…The previously published study indicated that organic pig meat was characterised by higher lipid stability compared with meat from conventional production system (Karwowska & Dolatowski, ). It was also indicated that the production system had no effect on haem iron content and myoglobin oxidation during storage.…”
Section: Introductionmentioning
confidence: 97%